40 Frailty deserves a mention in the new uk palliative medicine specialty training curriculum. A meta-synthesis and delphi study to establish appropriate content. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Dewhurst, Felicity; Paes, Paul; Hanratty, Barbara; Frew, Katie; Byrne-Davis, Lucie
Abstract : Background: Frailty, a decline in reserve, strength and endurance through deficit accumulation, is very common and highly associated with morbidity and mortality. Understanding how to provide palliative care for frail individuals is an international priority. Despite this, frailty is not mentioned in the current UK Palliative Medicine Specialty training curriculum (UK-PMSTC). Aim: To synthesise the literature and establish expert consensus on what should be included in a frailty subsection of the UK-PMSTC. This could be referenced by the new curriculum which is due to come into practice in 2022. Methods: Setting/Participants The Delphi panel were Subject Matter Experts(SME): Specialist Palliative Medicine Consultants (n=14) and Trainees (n=10) with representation from seven hospital trusts (n=19), seven community services (n=13), nine inpatient units/hospices (n=18) and care home services (n=one) (individuals work across multiple sites). Design Literature Meta-synthesis produced a draft curriculum with Bologna based learning outcomes (LO). The Delphi Study used standard methods and asked SME to rate LO importance for specialist-training completion and provided opportunity to add LO. Process was repeated until 70% consensus was achieved in over 90% of LO. SME divided LO into specific (for inclusion in a frailty subsection) or generic (applicable to other palliative conditions). Results: The meta-synthesis produced 113 LO, two were added by SME. Three Delphi rounds concluded 86 LO were specific to frailty whilst 29 were generic. Of the 86 items; 47 were considered essential, 34 desirable and five unnecessary. LO were arranged using clinical practice domains and bloom's taxonomy. Conclusions: We have developed a frailty curriculum that could be used as a subsection for the UK-PMSTC, highlighting the complex and unique palliative needs of those with frailty. Future research is required to inform implementation, educational-delivery and service-provision.